The COVID‐19 Yorkshire Rehabilitation Scale (C19‐YRS): Application and psychometric analysis in a post‐COVID‐19 syndrome cohort. Issue 3 (5th November 2021) - O'Connor, Rory J.; Preston, Nick; Parkin, Amy; Makower, Sophie; Ross, Denise; Gee, Jeremy; Halpin, Stephen J.; Horton, Mike; Sivan, Manoj
Abstract: As our understanding of the nature and prevalence of post‐coronavirus disease 2019 (COVID‐19) syndrome (PCS) is increasing, a measure of the impact of COVID‐19 could provide valuable insights into patients' perceptions in clinical trials and epidemiological studies as well as routine clinical practice. To evaluate the clinical usefulness and psychometric properties of the COVID‐19 Yorkshire Rehabilitation Scale (C19‐YRS) in patients with PCS, a prospective, observational study of 187 consecutive patients attending a post‐COVID‐19 rehabilitation clinic was conducted. The C19‐YRS was used to record patients' symptoms, functioning, and disability. A global health question was used to measure the overall impact of PCS on health. Classical psychometric methods (data quality, scaling assumptions, targeting, reliability, and validity) were used to assess the C19‐YRS. For the total group, missing data were low, scaling and targeting assumptions were satisfied, and internal consistency was high (Cronbach's α = 0.891). Relationships between the overall perception of health and patients' reports of symptoms, functioning, and disability demonstrated good concordance. This is the first study to examine the psychometric properties of an outcome measure in patients with PCS. In this sample of patients, the C19‐YRS was clinically useful and satisfied standard psychometric criteria, providing preliminary evidence of its suitability as a measure of PCS.